Demonstration of 68Ga-prostate-specific Membrane Antigen Uptake in Metastatic Pancreatic Neuroendocrine Tumor - Prabhu, Meghana (Indian J Nucl Med, 2018)
We present the case of a 47-year-old female with metastatic pancreatic neuroendocrine tumor (NET). The patient was treated with long-acting octreotide which failed to halt disease progression. The patient was being considered for 177Lu-peptide receptor radionuclide therapy, and a 68Ga-DOTANOC positron emission tomography-computed tomography (PET-CT) was acquired initially, which showed good uptake in the primary and metastatic lesions. Metastatic pancreatic NETs have limited treatment options, and given the background that these tumors are highly vascular and prostate-specific membrane antigen (PSMA) expression is known in the endothelium of tumor neovasculature, we decided to perform a 68Ga-PSMA-HBED-CC PET-CT scan. It revealed radiotracer uptake in the metastatic liver lesions although not as high as 68Ga-DOTANOC-PET-CT. PSMA expression needs to be researched further, especially in high-grade NETs where somatostatin expression may be poor.